TOXIC WORDS IN ONLINE GAME MOBILE LEGENDS: BANG BANG - Keintjem, Livio; Posumah, Jennie; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to describe what toxic words are revealed in the online game Mobile Legends: Bang Bang. In completing this study, researcher analyzed the words and behavior of Mobile Legends: Bang Bang players by watching the content on their Youtube channels. The result of this study explained that in online game content Mobile Legends: Bang Bang on the Luthfil 286 Youtube account, Brandon Kent Everything, and Oura Gaming there are 268 toxic words such as anjing, babi, goblok, anak dajjal, bangsat, tai laso and others. recommendation for online game players, it was hoped that they could keep words and actions, so that they could make this online game an entertainment platform instead of shedding their emotions and resenting each other.